High-strength fiber composite material based on aramid 1414 fiber and preparation method thereof
By subjecting aramid 1414 fibers to plasma treatment and coating, combined with hot pressing or vacuum-assisted molding processes, the mechanical strength and chemical resistance of aramid 1414 fiber composites were solved, achieving the preparation of high-strength, lightweight, and environmentally stable composite materials.
Patent Information
- Application Number
- CN202511442691.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-10
- Publication Date
- 2025-11-25
AI Technical Summary
How to further improve the mechanical strength and chemical resistance of aramid 1414 fiber composites.
Plasma treatment was used to modify the surface of aramid 1414 fibers to form polar functional groups to improve compatibility with the resin matrix. The interfacial bonding was enhanced by the synergistic effect of silane coupling agent KH-560, bisphenol A type epoxy resin and nano titanium dioxide. The composite material was prepared by hot pressing or vacuum-assisted resin transfer molding.
It significantly improves the mechanical properties of composite materials, including tensile strength, flexural strength and compressive strength, while maintaining low density characteristics, enhancing the environmental stability and impact resistance of the material, and making it suitable for high temperature and harsh environments.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention belongs to the field of composite material technology, specifically a high-strength fiber composite material based on aramid 1414 fiber and its preparation method. Background Technology
[0002] Aramid 1414 fiber, also known as poly(p-phenylene terephthalamide) fiber, has found wide application in aerospace, aviation, transportation, and communications fields due to its low density, high specific strength, high temperature resistance, non-flammability, non-melting, and creep resistance. The demand for this fiber is increasing year by year, especially in areas such as communication cable reinforcement, high-pressure storage tanks, bulletproof vests, high-pressure containers, aramid pulp, coal mine conveyor belts, sporting goods, and high-end car tire cords, demonstrating enormous potential. Currently, the production capacity of aramid fiber abroad is mainly concentrated in the United States, Japan, and Europe, while the industrialization of aramid fiber in China has also made significant progress. Both domestic and international researchers have shown great interest and investment in the research and application of aramid fiber.
[0003] Due to its unique properties, the market demand for aramid 1414 fiber has been increasing year by year. Especially in the field of high-performance composite materials, the application of aramid 1414 fiber is considered one of the key factors in improving product performance. Although the preparation technology of aramid 1414 fiber itself is relatively mature, there are still some challenges in the further development of its application technology. For example, how to improve the bonding force between the fiber and the resin matrix, and how to improve the overall performance of composite materials by optimizing process parameters. Summary of the Invention
[0004] The technical problem to be solved by this invention is: how to further improve the mechanical strength and chemical resistance of composite materials based on aramid 1414 fiber.
[0005] To achieve the above technical objectives, the present invention adopts the following technical solution: A high-strength fiber composite material based on aramid 1414 fiber, comprising the following components by weight percentage: 60%~80% aramid 1414 fiber and 20%~40% resin matrix; wherein the aramid 1414 fiber undergoes surface treatment and dimensional stabilization treatment; the surface treatment involves plasma treatment modification of the aramid 1414 fiber surface at room temperature and pressure (to improve its compatibility with the resin matrix), with a treatment power of 30W / cm². 3 ~35W / cm 3The discharge gap is 1.2mm~1.5mm, the processing time is 3~4 seconds, the processing gas is oxygen, and the processed fibers are collected in the take-up roller; the size stabilization treatment is as follows: the surface-treated aramid 1414 fibers are immersed in a solution containing a coating material, wherein the weight ratio of the coating material solution is 1~2 parts of silane coupling agent KH-560, 30~40 parts of bisphenol A type epoxy resin, 5~10 parts of nano titanium dioxide, and 56.5 parts of cyclohexane solvent.
[0006] In the above technical solutions, oxygen plasma treatment of aramid 1414 fibers can form new polar functional groups on the fiber surface. The introduction of these polar functional groups increases the total surface free energy of the fiber surface, thereby improving the wettability of the fiber surface. Plasma treatment can also increase the roughness of the fiber surface, forming more grooves and undulations, further enhancing the physical anchoring effect between the fiber and the resin.
[0007] Furthermore, an appropriate amount of silane coupling agent KH-560 can provide good interfacial adhesion, bisphenol A epoxy resin can increase the compatibility between aramid fibers and the resin matrix, and nano-titanium dioxide can improve the surface roughness and chemical activity of aramid fibers. These three components synergistically improve the dimensional stability of aramid 1414 fibers, reduce deformation caused by environmental changes, and enhance the interfacial bonding between the fiber and the resin matrix. After impregnation treatment, subsequent heat treatment and curing ensures the formation of stable chemical bonds between the resin matrix and the aramid fiber surface.
[0008] Preferably, the composite material is composed of the following components by weight percentage: 60%~80% aramid 1414 fiber and 20%~40% resin matrix.
[0009] Preferably, the resin matrix is selected from one or more of epoxy resin, phenolic resin, and polyurethane resin.
[0010] Preferably, the composite material has a tensile strength of 1500MPa to 1600MPa, a flexural strength of 1000MPa to 1070MPa, and a compressive strength of 1200MPa to 1300MPa.
[0011] Preferably, the diameter of the aramid 1414 fiber is 5 to 15 micrometers.
[0012] Based on the above technical solutions, the present invention further provides a method for preparing the above-mentioned composite material, comprising the following steps: 1) The aramid 1414 fiber is subjected to the aforementioned surface treatment and the aforementioned dimensional stabilization treatment in sequence; 2) Wrap the aramid 1414 fibers treated in step 1) onto the resin matrix according to the specified proportions; 3) The composite material is obtained by heat treatment and curing.
[0013] Preferably, the heat treatment curing is performed by hot pressing, with a temperature of 120℃~180℃ and a pressure of 5MPa~15MPa. This hot pressing process can significantly improve the performance of aramid 1414 fiber-reinforced composite materials. The preferred temperature conditions facilitate the full curing of the resin matrix and aramid fibers, thereby forming a stable three-dimensional network structure and enhancing the mechanical properties of the material. Hot pressing at the preferred temperature and pressure can effectively reduce internal residual stress and improve the dimensional stability and consistency of the product.
[0014] Preferably, the heat treatment curing is vacuum-assisted resin transfer molding, comprising the following steps: placing a resin matrix coated with aramid 1414 fibers into a mold and then evacuating to remove air bubbles; then accelerating the curing process at a temperature of 60°C to 100°C. When preparing high-strength fiber composites based on aramid 1414 fibers using vacuum-assisted resin transfer molding (VARTM), curing at a temperature of 60°C to 100°C can accelerate the curing reaction and shorten the curing cycle. Removing air bubbles through vacuum significantly reduces the porosity of the composite material, enhances the interfacial bonding between the fibers and the resin matrix, and thus improves the overall mechanical properties of the material. The VARTM process is particularly suitable for manufacturing large or complex-shaped components.
[0015] Compared with the prior art, the beneficial effects of the present invention are: The composite material of this invention utilizes the high strength and high modulus properties of aramid 1414 fiber to provide excellent mechanical properties, including high tensile strength, high flexural strength, and high compressive strength. Thanks to the low density of aramid 1414 fiber, the composite material achieves lightweighting while maintaining high strength. The high-temperature resistance of aramid 1414 fiber enables the composite material to maintain stable performance in high-temperature environments, making it suitable for high-temperature operating environments. The impact resistance of this composite material is significantly improved, effectively absorbing and dispersing impact energy. This material also exhibits good environmental stability, maintaining its performance under various environmental conditions, including harsh environments such as humid heat and salt spray, making it suitable for outdoor equipment and structural components exposed to natural environments for extended periods. The composite material of this invention not only possesses excellent mechanical properties but also achieves a balance between cost-effectiveness and production efficiency through optimized manufacturing processes, demonstrating broad market application prospects. Detailed Implementation
[0016] The specific embodiments of the present invention will be described in detail below. To avoid excessive and unnecessary detail, well-known structures or functions will not be described in detail in the following embodiments. The approximate language used in the following embodiments is for quantitative purposes, indicating that a certain degree of variation in quantity is permissible without changing the basic function. Unless otherwise defined, the technical and scientific terms used in the following embodiments have the same meaning as commonly understood by those skilled in the art to which this invention pertains.
[0017] Example 1: Prepare aramid 1414 fibers and resin matrix, wherein the weight percentage of aramid 1414 fibers is 70% and the weight percentage of resin matrix is 30%.
[0018] Surface treatment of aramid 1414 fibers was performed using plasma treatment modification at a power of 30 W / cm. 3 The discharge gap is 1.2 mm, the processing time is 3 seconds, and the processing gas is oxygen.
[0019] Dimensional stabilization treatment was performed by immersing the surface-treated aramid 1414 fibers in a solution containing a coating material. The coating material solution was formulated with the following weight ratios: 1 part silane coupling agent KH-560, 35 parts bisphenol A epoxy resin, 7 parts nano titanium dioxide, and 56.5 parts cyclohexane solvent.
[0020] The pretreated aramid 1414 fibers are wound onto the resin matrix.
[0021] Composite materials were prepared by hot pressing and curing at a temperature of 120°C and a pressure of 5 MPa.
[0022] Example 2: Prepare aramid 1414 fibers and a resin matrix, wherein the weight percentage of aramid 1414 fibers is 75% and the weight percentage of the resin matrix is 25%.
[0023] Surface treatment of aramid 1414 fibers was performed using plasma treatment modification at a power of 35 W / cm. 3 The discharge gap is 1.5 mm, the processing time is 4 seconds, and the processing gas is oxygen.
[0024] Dimensional stabilization treatment was performed by immersing the surface-treated aramid 1414 fibers in a solution containing a coating material. The coating material solution was formulated with the following weight proportions: 2 parts silane coupling agent KH-560, 30 parts bisphenol A epoxy resin, 10 parts nano titanium dioxide, and 56.5 parts cyclohexane solvent.
[0025] The pretreated aramid 1414 fibers are wound onto the resin matrix.
[0026] Composite materials were prepared by vacuum-assisted resin transfer molding and curing. The resin matrix wrapped with aramid 1414 fibers was placed into the mold and then vacuumed to remove air bubbles. The curing process was then accelerated at 80°C.
[0027] Example 3: Prepare aramid 1414 fibers and resin matrix, wherein the weight percentage of aramid 1414 fibers is 60% and the weight percentage of resin matrix is 40%.
[0028] Surface treatment of aramid 1414 fibers was performed using plasma treatment modification at a power of 30 W / cm. 3 The discharge gap is 1.2 mm, the processing time is 3 seconds, and the processing gas is oxygen.
[0029] Dimensional stabilization treatment was performed by immersing the surface-treated aramid 1414 fibers in a solution containing a coating material. The coating material solution had the following weight ratios: 1.5 parts silane coupling agent KH-560, 37.5 parts bisphenol A epoxy resin, 8 parts nano titanium dioxide, and 56.5 parts cyclohexane solvent.
[0030] The pretreated aramid 1414 fibers are wound onto the resin matrix.
[0031] Composite materials were prepared by hot pressing and curing at a temperature of 150°C and a pressure of 10 MPa.
[0032] Example 4: Prepare aramid 1414 fibers and a resin matrix, wherein the weight percentage of aramid 1414 fibers is 80% and the weight percentage of the resin matrix is 20%.
[0033] Surface treatment of aramid 1414 fibers was performed using plasma treatment modification at a power of 35 W / cm. 3 The discharge gap is 1.5 mm, the processing time is 4 seconds, and the processing gas is oxygen.
[0034] Dimensional stabilization treatment was performed by immersing the surface-treated aramid 1414 fibers in a solution containing a coating material. The coating material solution was formulated with the following weight ratios: 1 part silane coupling agent KH-560, 40 parts bisphenol A epoxy resin, 5 parts nano titanium dioxide, and 56.5 parts cyclohexane solvent.
[0035] The pretreated aramid 1414 fibers are wound onto the resin matrix.
[0036] Composite materials were prepared by vacuum-assisted resin transfer molding and curing. The resin matrix wrapped with aramid 1414 fibers was placed into the mold and then vacuumed to remove air bubbles. The curing process was then accelerated at 60°C.
[0037] Example 5: Prepare aramid 1414 fibers and resin matrix, wherein the weight percentage of aramid 1414 fibers is 70% and the weight percentage of resin matrix is 30%.
[0038] Surface treatment of aramid 1414 fibers was performed using plasma treatment modification at a power of 30 W / cm. 3 The discharge gap is 1.2 mm, the processing time is 3 seconds, and the processing gas is oxygen.
[0039] Dimensional stabilization treatment was performed by immersing the surface-treated aramid 1414 fibers in a solution containing a coating material. The coating material solution was formulated with the following weight proportions: 2 parts silane coupling agent KH-560, 30 parts bisphenol A epoxy resin, 10 parts nano titanium dioxide, and 56.5 parts cyclohexane solvent.
[0040] The pretreated aramid 1414 fibers are wound onto the resin matrix.
[0041] Composite materials were prepared by hot pressing and curing at a temperature of 180℃ and a pressure of 15MPa.
[0042] Example 6: Prepare aramid 1414 fibers and a resin matrix, wherein the weight percentage of aramid 1414 fibers is 75% and the weight percentage of the resin matrix is 25%.
[0043] Surface treatment of aramid 1414 fibers was performed using plasma treatment modification at a power of 35 W / cm. 3 The discharge gap is 1.5 mm, the processing time is 4 seconds, and the processing gas is oxygen.
[0044] Dimensional stabilization treatment was performed by immersing the surface-treated aramid 1414 fibers in a solution containing a coating material. The coating material solution had the following weight ratios: 1.5 parts silane coupling agent KH-560, 35 parts bisphenol A epoxy resin, 7.5 parts nano titanium dioxide, and 56.5 parts cyclohexane solvent.
[0045] The pretreated aramid 1414 fibers are wound onto the resin matrix.
[0046] Composite materials were prepared by vacuum-assisted resin transfer molding and curing. A resin matrix wrapped with aramid 1414 fibers was placed into a mold and then vacuumed to remove air bubbles. The curing process was then accelerated at 100°C.
[0047] Example 7: Prepare aramid 1414 fibers and resin matrix, wherein the weight percentage of aramid 1414 fibers is 60% and the weight percentage of resin matrix is 40%.
[0048] Surface treatment of aramid 1414 fibers was performed using plasma treatment modification at a power of 30 W / cm. 3 The discharge gap is 1.2 mm, the processing time is 3 seconds, and the processing gas is oxygen.
[0049] Dimensional stabilization treatment was performed by immersing the surface-treated aramid 1414 fibers in a solution containing a coating material. The coating material solution was formulated with the following weight ratios: 1 part silane coupling agent KH-560, 30 parts bisphenol A epoxy resin, 5 parts nano titanium dioxide, and 56.5 parts cyclohexane solvent.
[0050] The pretreated aramid 1414 fibers are wound onto the resin matrix.
[0051] Composite materials were prepared by hot pressing and curing at a temperature of 120°C and a pressure of 5 MPa.
[0052] Example 8: Prepare aramid 1414 fibers and resin matrix, wherein the weight percentage of aramid 1414 fibers is 80% and the weight percentage of resin matrix is 20%.
[0053] Surface treatment of aramid 1414 fibers was performed using plasma treatment modification at a power of 35 W / cm. 3 The discharge gap is 1.5 mm, the processing time is 4 seconds, and the processing gas is oxygen.
[0054] Dimensional stabilization treatment was performed by immersing the surface-treated aramid 1414 fibers in a solution containing a coating material. The coating material solution was formulated with the following weight proportions: 2 parts silane coupling agent KH-560, 40 parts bisphenol A epoxy resin, 10 parts nano titanium dioxide, and 56.5 parts cyclohexane solvent.
[0055] The pretreated aramid 1414 fibers are wound onto the resin matrix.
[0056] Composite materials were prepared by vacuum-assisted resin transfer molding and curing. A resin matrix wrapped with aramid 1414 fibers was placed into a mold and then vacuumed to remove air bubbles. The curing process was then accelerated at 100°C.
[0057] Comparative Example 1: Prepare aramid 1414 fibers and resin matrix, wherein the weight percentage of aramid 1414 fibers is 60% and the weight percentage of resin matrix is 40%.
[0058] The aramid 1414 fiber was surface treated with chemical treatment instead of plasma treatment. It was treated with 5% NaOH solution for 30 minutes, then washed with water until neutral and dried.
[0059] To achieve dimensional stabilization, instead of using a coating material solution, the surface-treated aramid 1414 fibers were subjected to hot air drying at 105°C for 2 hours.
[0060] The pretreated aramid 1414 fibers are wound onto the resin matrix.
[0061] Composite materials were prepared by hot pressing and curing at a temperature of 120°C and a pressure of 5 MPa.
[0062] In Comparative Example 1, chemical treatment was used instead of plasma treatment, which affects the chemical properties and roughness of the fiber surface, thus affecting the bonding between the fiber and the resin. Furthermore, the dimensional stabilization treatment in Comparative Example 1 used hot air drying instead of impregnation with a coating material solution, which reduces the dimensional stability of the fiber and the overall performance of the composite material.
[0063] Comparative Example 2: Prepare aramid 1414 fibers and resin matrix, wherein the weight percentage of aramid 1414 fibers is 80% and the weight percentage of resin matrix is 20%.
[0064] The surface treatment of aramid 1414 fibers was performed without plasma modification, but instead with ultraviolet irradiation at an intensity of 80 mW / cm². 2 Irradiation time: 5 minutes.
[0065] Dimensional stabilization treatment was performed by immersing the surface-treated aramid 1414 fibers in a solution containing a coating material. The coating material solution was formulated with the following weight ratios: 0 parts silane coupling agent KH-560, 40 parts bisphenol A epoxy resin, 5 parts nano titanium dioxide, and 56.5 parts cyclohexane solvent.
[0066] The pretreated aramid 1414 fibers are wound onto the resin matrix.
[0067] Composite materials were prepared by vacuum-assisted resin transfer molding and curing. The resin matrix wrapped with aramid 1414 fibers was placed into the mold and then vacuumed to remove air bubbles. The curing process was then accelerated at 80°C.
[0068] While ultraviolet irradiation treatment in Comparative Example 2 may also introduce new chemical groups, its effect on increasing the interfacial bonding between the fiber and the resin matrix is significantly less than that of this invention. The size stabilization treatment in Comparative Example 2 omitted the silane coupling agent KH-560, which weakens the interfacial bonding between the fiber and the resin matrix.
[0069] The composite material samples prepared in the examples and comparative examples were subjected to performance tests, and the test results are shown in Table 1. Tensile strength testing followed ISO 527-4 standard, representing the maximum load-bearing capacity of the material during tension, in MPa. Flexural strength testing followed GB / T 1449-2005 standard, representing the maximum load-bearing capacity of the material under flexural load, in MPa. Compressive strength testing followed ASTM D6641 / D6641M standard, representing the maximum load-bearing capacity of the material under compressive load, in MPa.
[0070] Table 1. Mechanical property test results of the composite materials obtained in each embodiment and comparative example.
[0071] The experimental results above show that the tensile strength, flexural strength, and compressive strength of the composite materials obtained in Examples 1-8 are all superior to those in Comparative Examples 1 and 2, indicating that the surface treatment and dimensional stabilization process of aramid 1414 fiber in this invention can significantly improve the overall performance of the composite material. Among them, Example 2 achieved the best mechanical properties, with tensile strength, flexural strength, and compressive strength reaching 1601 MPa, 1074 MPa, and 1308 MPa, respectively. Combined with the existing low-density characteristics of aramid 1414 fiber, the composite material fully realizes its lightweight and high-strength performance characteristics.
[0072] The embodiments of the present invention have been described in detail above, but the content described is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, and improvements made within the scope of the present invention should be included within the protection scope of the present invention.
Claims
1. A high-strength fiber composite material based on aramid 1414 fiber, characterized in that, The composite material comprises the following components by weight percentage: 60%~80% aramid 1414 fiber and 20%~40% resin matrix; wherein the aramid 1414 fiber undergoes surface treatment and dimensional stabilization treatment; the surface treatment involves plasma modification of the aramid 1414 fiber surface at room temperature and pressure, with a treatment power of 30W / cm. 3 ~35W / cm 3 The discharge gap is 1.2mm~1.5mm, the processing time is 3~4 seconds, the processing gas is oxygen, and the processed fibers are collected in the take-up roller; the size stabilization treatment is as follows: the surface-treated aramid 1414 fibers are immersed in a solution containing a coating material, wherein the weight ratio of the coating material solution is 1~2 parts of silane coupling agent KH-560, 30~40 parts of bisphenol A type epoxy resin, 5~10 parts of nano titanium dioxide, and 56.5 parts of cyclohexane solvent.
2. The high-strength fiber composite material based on aramid 1414 fiber according to claim 1, characterized in that, The composite material is composed of the following components by weight percentage: 60%~80% aramid 1414 fiber and 20%~40% resin matrix.
3. The high-strength fiber composite material based on aramid 1414 fiber according to claim 1, characterized in that, The resin matrix is selected from one or more of epoxy resin, phenolic resin, and polyurethane resin.
4. The high-strength fiber composite material based on aramid 1414 fiber according to claim 1, characterized in that, The composite material has a tensile strength of 1500MPa to 1600MPa, a flexural strength of 1000MPa to 1070MPa, and a compressive strength of 1200MPa to 1300MPa.
5. A high-strength fiber composite material based on aramid 1414 fiber according to claim 1, characterized in that, The diameter of the aramid 1414 fiber is 5-15 micrometers.
6. A method for preparing the composite material according to any one of claims 1 to 5, characterized in that, Includes the following steps: 1) The aramid 1414 fiber is subjected to the aforementioned surface treatment and the aforementioned dimensional stabilization treatment in sequence; 2) Wrap the aramid 1414 fibers treated in step 1) onto the resin matrix according to the specified proportions; 3) The composite material is obtained by heat treatment and curing.
7. The preparation method according to claim 6, characterized in that, The heat treatment curing is hot pressing, with a temperature of 120℃~180℃ and a pressure of 5MPa~15MPa.
8. The preparation method according to claim 6, characterized in that, The heat treatment curing is a vacuum-assisted resin transfer molding process, which includes the following steps: after placing the resin matrix wrapped with aramid 1414 fibers into the mold, a vacuum is drawn to remove air bubbles; then the curing process is accelerated at a temperature of 60℃~100℃.
Citation Information
Cited By
Aramid fiber / epoxy resin composite material and preparation method thereof
CN121268100A
Aramid fiber / epoxy resin composite material and a method for preparing the same
CN121268100B